Sanksi Pidana Pencucian Uang Hasil Kejahatan Narkotika - Wan Darmayan Achmayu (International Forum of Researchers and Lecturers, 2023)
Whereas the legal regulation governing the Criminal Sanctions for Money Laundering of Narcotics Crimes is Article 2 of Law Number 8 of 2010 Concerning the Prevention and Eradication of Money Laundering Crimes paragraph (1) point 3 concerning Narcotics. The implementation of the implementation of the Criminal Sanctions for Money Laundering from Narcotics Crime is still overlapping and separate or simultaneous. This occurs both at the placement stage, the distribution stage, and the collection stage, so that handling becomes increasingly difficult and requires systematic and continuous capacity building. Factors constraining Criminal Sanctions for Money Laundering from Narcotics Crime are the Globalization Factor, the Rapid Technological Advancement Factor, the Very Strict Bank Confidential Provisions Factor of the Country Concerned. Therefore, stricter legal arrangements are needed in enforcing criminal sanctions for money laundering of the proceeds of narcotics crimes and should pay more attention to the principles of simple, fast and low-cost criminal procedural law so that the next stage of the judicial process can be carried out immediately.